Pengaruh risk profile, good corporate governance (GCG), earnings (profitability), and capital (capital adequacy), terhadap pertumbuhan laba pada bank syariah - Putri, Salsabila Fadila; Yunita, Irni (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The development of the financial sector, particularly the banking industry, has a significant impact on the economic growth of a country. Islamic banks, as part of the financial sector, play a crucial role in supporting economic growth and financial stability. This study aims to analyze the influence of bank health levels, assessed based on Risk Profile (Profil resiko), Good Corporate Governance (GCG), Earnings (Profitability), and Capital (Capital Adequacy), on profit growth in Sharia Banks listed on the Indonesia Stock Exchange (IDX) during the period 2018-2022. Secondary data used were financial reports published by relevant Islamic banks or the Financial Services Authority (OJK) website with 4 companies as samples. Quantitative method was chosen for this paper. Limitation for this paper is only for sharia banks listed on Bursa Efek Indonesia (BEI). First, from the test on the Influence of Risk Profile (Non Performing Loan/NPL) on Profit Growth, the results show that NPL has an insignificant negative influence on profit growth. Second, in the test on the Influence of Good Corporate Governance (GCG) on Profit Growth, although the coefficient shows a positive influence, partially GCG does not have a significant influence on the company's profit growth. Third, the test on the Influence of Rentability (Return On Asset/ROA) on Profit Growth shows that ROA has a positive influence, but is not significant on the company's profit growth. Fourth, in the test on the Influence of Capital (Capital Adequacy Ratio/CAR) on Profit Growth, although the coefficient shows a positive influence, partially CAR does not have a significant influence on the company's profit growth.The results of this research are expected to provide a better understanding of the factors influencing the profit growth of Islamic banks and their implications for the stability and growth of the Islamic financial sector, for investor to get maximal capital gain. The weakness and limitation of the study the samples are only 4 companies.